THE STABILITY ESTIMATION OF AUTOMATIC CONTROL FEEDBACK SYSTEMS UPON THE CONDITION THAT MEANSQUARED ERRORS MINIMIZATION AND QUADRATIC INTEGRAL ESTIMATION OF PHASE LOCK LOOP SYSTEM TRANSIENT PROCESSES - Yevhen V. Lebid (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
In the article presented results analysis principles construction the system phase - locked loop (PLL) is on the example the tracker system. Dependences amplification the system, meansquared error and quadratic integral estimation transients the system phase - locked loop (PLL) factor are investigational. The presented results allow improving dynamic description the system phase - locked loop (PLL) in radiotechnical facilities the special setting.